SWPlan Software Application for Malaysian Municipal Solid Waste Management - S. H, Fauziah; P, Agamuthu (Malaysian Journal of Science, 2007)
Among the biggest and most serious issues faced by a nation due to the impacts of urbanization and population explosions the rate of waste generation. Per capita generation in Peninsular Malaysia is approximately 1.2 kg of municipal solid waste (MSW) everyday which amounts to 18,000 tonnes. Application of various tools to determine the efficiency of a system has been very helpful in minimizing costs and optimizing a desired system. This study was conducted to design an integrated solid waste management system and to determine the best integrated technology in terms of efficiency, cost and performance. SWPlan software was utilized to determine the appropriate waste management approaches including waste reduction, recycling, composting, waste-to-energy conversion, landfill disposal and others. The software was able to determine the capital operating cost and management costs, by taking into consideration the possible revenues from alternate options of waste disposal. Among the options which were examined included refuse derived fuel (RDF) conversion, recycling activities and other by-products from waste treatment options such as composting. In order to evaluate the potentials of SWPlan, information on population density, waste composition and amount were defined according to data obtained from waste management studies conducted earlier. Results indicated that waste generated by communities in Selangor in particular and Malaysians in general composed of a high percentage of organic waste, accounting for approximately 46% of the total tonnage. The option of composting, including yard waste composting and MSW composting were derived from the software application as it was found to offer the best system with the consideration of cost and energy efficiency. Findings also indicated the possibility of implementing RDF conversion to divert the waste stream which not only reduced the disposal cost but also generated significant amounts of revenue for waste managers. The other viable application is recycling. The application of SWPlan to MSW management in Malaysia optimized the economical aspects of the management and would reduce the existing environmental impacts due to improper waste disposal system currently practiced in the country.